Fluid & Electrolytes in Clinical Practice - Mostafi, Mamun (Bangladesh Journal of Medicine, 2023)
Despite the fact that fluid and electrolyte preparations are the most commonly prescribed medications in hospitals, a number of studies have shown that the knowledge and practice of fluid and electrolytebalance among young doctors is suboptimal, possibly due to inadequate attention to this most common but less taught chapter. This is responsible for errors in management, which continue to cause avoidable morbidity and even mortality. This presentation is aimed to create interest and further studies amongst the physician to assist them in understanding and solving some of the most common practical issuesof day- to-day clinical practice. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 180